2005
DOI: 10.1080/08035250500434793
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic evaluation of milk from different mammalian species as a substitute for breast milk

Abstract: Proteomic evaluation of milk from different mammalian species may not only be of help when recommending suitable feeding in cases of cows' milk allergy but also gives new insight into the background to allergic reactions caused by milk proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…In vitro studies suggest antibody cross-reactivity and demonstrate a similar proteomic evaluation between cow and water buffalo’s milk proteins. 11,12 Similarly, one human study from Israel showed a high degree of skin test positivity to water buffalo’s milk in patients with cow’s milk allergy. 13 In contrast, a recent case report discussed a child with cow’s milk allergy who was able to tolerate water buffalo’s milk.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies suggest antibody cross-reactivity and demonstrate a similar proteomic evaluation between cow and water buffalo’s milk proteins. 11,12 Similarly, one human study from Israel showed a high degree of skin test positivity to water buffalo’s milk in patients with cow’s milk allergy. 13 In contrast, a recent case report discussed a child with cow’s milk allergy who was able to tolerate water buffalo’s milk.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the intake of mammalian milks during the first year of life, donkey’s milk has a proteomic profile similar to human milk [46] and it has been demonstrated well tolerated in clinical studies performed on cow’s milk allergic children aged 12 months or above [47,48]. …”
Section: Introductionmentioning
confidence: 99%
“…Donkey's milk (DM) has a lower protein content than other mammalians' milk, and also its proteomic profile is similar to breast milk [16], it has an acceptable taste, and it is less expensive than eHF. However, it is poor in lipids, and it has a low caloric value with respect to human milk and other mammalians' milk [17], that represents a limit to its employment in the toddler's diet.…”
Section: Introductionmentioning
confidence: 99%